Performance analysis of shear horizontal one port surface acoustic wave (SAW) resonator for optimal liquid sensing based on finite element method - Yih Bing Chu (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper presents the numerical study using finite element method for optimal liquid sensing performance of one port surface acoustic wave (SAW) resonator. Simulation shows that the extend of IDT-reflector gap can be optimized to contain most of the piezoelectric displacement. Various settings of liquid placement on the mentioned region yield distinct resonant frequency responses of the SAW sensor. For concentrated liquid with higher order of viscosity, magnitude of S-Parameter and phase of the propagating SAW can be applied to sense the liquid solutions. Based on the results, optimal liquid sensing performance of the device can be achieved when liquid droplet sized about 10 % of the aperture is placed in the middle position of the IDT-reflector gap conditioned at 1.5 λ. Using the formulated strategy, the one port SAW device distinguishes well 0 % to 100 % glycerine concentrations compared to limited detection range reported in the previous study. The finding includes equation of liquid turnover viscosity before shift in direction of the changes in S-Parameter measurement. The derived parameters can be set as reference to design the microfludic cell or lab-on-chip based on the one port SAW configuration for optimized liquid sensing performance.